ANALISIS PERBANDINGAN PELACAKAN OBJEK MENGGUNAKAN OPTICAL FLOW DAN BACKGROUND ESTIMATION PADA KAMERA BERGERAK - Wahyu Supriyatin (ILKOM Jurnal Ilmiah, 2019)
Object tracking is one of computer vision. Can be developed into various based applications like human computers interface, video compression and security system. Object tracking is used to identified objects within background and identify the number of objects that a cross. Algorithm for this object tracking use optical flow method and background estimation. Testing is carried out using a moving camera placed in a car. It's using parameter values for each Algorithm. The test is used three videos from the Matlab. Simulink Profile Report that optical flow method had Recorded Total Time better than the background estimation with 100 seconds duration. The optical flow Testing method successfully identified the car object. And background testing didn't succeed in identified and to differentiate an object to it’s background. The object test recorded from the distance with a camera, to examined how many the background was and the speed of cars.